A Nomogram Predicting the Progression-Free Survival of Nonmetastatic Renal Cell Carcinoma Patients With Venous Thrombus After Surgery - Zhang, Yu; Tian, XiaoJun; Bi, Hai; Yan, Ye; Liu, Zhuo; Liu, Cheng; Zhang, ShuDong; Ma, LuLin (Frontiers in Oncology, 2022)
Purpose: To demonstrate the progression-free survival (PFS) of renal cell carcinoma (RCC) patients with venous thrombus after radical nephrectomy and venous thrombectomy (RN-VT) and to develop and validate a nomogram to predict the PFS of patients after RN-VT. Materials and Methods: We reported our prospective follow-up data of RCC patients with venous thrombus from January 2014 to September 2020. We used the Kalan-Meier method to assess the PFS. The Cox proportional hazards regression model was used to determine the predictors. Nomograms predicting the PFS was established and external validation was performed. Calibration curves and decision curves were generated to assess the predictive efficacy and clinical benefit. Results: After a median follow-up of 31 mon, 117 patients had disease progression and the median PFS was 29.0 mon (95% CI 24.7-33.3 mon). The 1-yr, 3-yr and 5-yr PFS were 78.9%, 45.4% and 28.2%, respectively. Multivariate analyses showed that severe complication (HR 2.29, 95% CI 1.41-3.73, P=0.001), Fuhrman grade (grade-4 HR 1.67, 95% CI 1.11-2.51, P=0.02), pathological type (papillary RCC HR 1.82, 95% CI 1.17-2.85, P=0.009; other RCC HR 2.59, 95% CI 1.41-4.76, P=0.002), perinephric fat invasion (HR 1.54, 95% CI 1.12-2.10, P=0.007), sarcomatoid differentiation (HR 2.57, 95% CI 1.62-4.07, P<0.001) and distant metastasis (HR 2.33, 95% CI 1.65-3.28, P<0.001) were associated with a worse PFS. Nomogram based on the predictors was externally validated to have good discrimination and calibration and could improve PFS prediction to obtain clinical benefit. Conclusions: We constructed and validated a nomogram to predict the 1-yr, 3-yr and 5-yr PFS of RCC patients with venous thrombus after surgery. The model can help identify patients who can benefit the most from surgery and develop the criteria for clinical trial enrollment.